MOSSBAUER STUDY OF SYNTHETIC MG0.22FE0.78SIO3 CLINOPYROXENE - Eeckhout S.G.; De Grave E.; McCammon C.A.; Vochten R. (My University, 2001)
Transmission Mössbauer spectra of synthetic Ca-free P21/c Mg0.22Fe0.78SiO3 clinopyroxene were collected at temperatures in the range 4.2 to 745K and in an external magnetic field of 60kOe at 180K. The magnetic order-disorder transition temperature was determined by Mössbauer thermoscanning to be 21 ± 3K. Above this temperature, all Mössbauer spectra consist of a superposition of two doublets, respectively produced by Fe2+ ions at an almost regular octahedral M1 site and at a more distorted octahedral M2 site. The temperature variation of the Fe2+ center shifts were analyzed using the Debye model for the lattice vibrations. The characteristic Mössbauer temperatures were found to be 356K ± 35K for M1 and 333K ± 25K for M2. From the external field (60kOe) Mössbauer spectrum recorded at 180 K, the principal component V zz of the electric field gradient (EFG) was determined to be positive for both sites but precise values for the magnitudes of the asymmetry parameters η of the EFG could not be determined. The temperature variations of the M1 and M2 quadrupole splittings ΔE Q(T) are consistent with the higher distortion of the M2 octahedra. Using the crystal-field model to interpret ΔE Q(T), the energy gaps δ1 and δ2 of the first excited electronic states within the 5D orbital term were estimated to be 410 ± 50 cm−1 and 730 ± 50 cm−1 for M1, and δ1=1050± 75 cm−1 for M2.